'Like ships in the night': A qualitative investigation of the impact of childhood cancer on parents' emotional and sexual intimacy. Issue 12 (6th October 2022) - Chow, Wan Ka; Hetherington, Kate; McGill, Brittany C.; Sansom‐Daly, Ursula M.; Daly, Rebecca; Miles, Gordon; Cohn, Richard J.; Wakefield, Claire E.
Abstract: Background: Childhood cancer is highly distressing for families and can place strain on parents' relationships. Parental functioning and cohesiveness are important predictors of family functioning and adaptation to stress. This qualitative study investigated the perceived impact of childhood cancer on parents' relationship with their partner, with a focus on emotional and sexual intimacy. Methods: We conducted semi‐structured interviews with 48 parents (42 mothers, six fathers) of children under the age of 18 who had completed curative cancer treatment. We analysed the interviews using thematic analysis. Results: At interview, parents were on average 40.7 years old (SD = 5.5, range: 29–55 years), and had a child who had completed cancer treatment between 3 months and 10.8 years previously ( M = 22.1 months). All participants were living with their partner in a married/de facto relationship. Most parents reported that their child's cancer treatment had a negative impact on emotional and sexual intimacy with their partner, with some impacts extending to the post‐treatment period. Reasons for compromised intimacy included exhaustion and physical constraints, having a shifted focus, and discord arising from different coping styles. Some parents reported that their relationship strengthened. Parents also discussed the impact of additional stressors unrelated to the child's cancer experience. Conclusions: Parents reported that childhood cancer had a negative impact on aspects of emotional and sexual intimacy, although relationship strengthening was also evident. It is important to identify and offer support to couples who experience ongoing relationship stress, which may have adverse effects on family functioning and psychological wellbeing into survivorship.